Up country - Carter, Alden R. (New York : Putnam, 1989)
When his mother's drinking problem causes him to spend several months with country relatives in upstate Wisconsin, sixteen-year-old Carl begins to build a new life for himself, only to see it threatened by a serious mistake from his painful past.
School Library Journal starred.
Wilson's Junior High School.
Wilson's Senior High School.
7.4
10-12
Young Adult
Keywords: Alcoholism -- Fiction; Country life -- Fiction; Family problems -- Fiction; Alcoholism -- Fiction; Country life -- Fiction; Family problems -- Fiction; Wisconsin -- Fiction; Wisconsin -- Fiction